Molecular underpinnings of the early brain developmental response to differential feeding in the honey bee Apis mellifera - Vieira, Joseana; de Paula Freitas, Flávia Cristina; Santos Cristino, Alexandre; Guariz Pinheiro, Daniel [UNESP]; Aguiar, Luiz Roberto; Framartino Bezerra Laure, Marcela Aparecida; Rosatto Moda, Lívia Maria; Paulino Simões, Zilá Luz; Barchuk, Angel Roberto (Elsevier, 2021)
Brain differential morphogenesis in females is one of the major phenotypic manifestations of caste development in honey bees. Brain diphenism appears at the fourth larval phase as a result of the differential feeding regime developing females are submitted during early phases of larval development. Here, we used a forward genetics approach to test the early brain molecular response to differential feeding leading to the brain diphenism observed at later developmental phases. Using RNA sequencing analysis, we identified 53 differentially expressed genes (DEGs) between the brains of queens and workers at the third larval phase. Since miRNAs have been suggested to play a role in caste differentiation after horizontal and vertical transmission, we tested their potential participation in regulating the DEGs. The miRNA-mRNA interaction network, including the DEGs and the royal- and worker-jelly enriched miRNA populations, revealed a subset of miRNAs potentially involved in regulating the expression of DEGs. The interaction of miR-34, miR-210, and miR-317 with Takeout, Neurotrophin-1, Forked, and Masquerade genes was experimentally confirmed using a luciferase reporter system. Taken together, our results reconstruct the regulatory network that governs the development of the early brain diphenism in honey bees.
Keywords: Development; Early brain; Gene expression; Honeybee; MicroRNA; Nutrition